Empowering voices, bridging cultures: Abracadabra 6.0 Pre-Diploma Poster Competition / Nur Fatin Shahmina Mohd Fauzey, Muhammad Aiman Abdul Halim and Aileen Farida Mohd Adam - Mohd Fauzey, Nur Fatin Shahmina; Abdul Halim, Muhammad Aiman; Mohd Adam, Aileen Farida (Academy of Language Studies, 2024)
On a vibrant Saturday, the 20th of January 2024, Laman Perdana was abuzz with the spirit of cultural exploration and linguistic excellence. The Abracadabra 6.0 Pre- Diploma Poster Competition under the inspiring theme ‘Guardians of Cultural Diversity’ unfolded its sixth chapter. This distinguished event, hosted by the Academy of Language Studies (APB) of UiTM Pulau Pinang Branch (UiTMCPP) is not merely a competition; it is a celebration of diversity, language, and the boundless potential of our students. This year, the competition saw the participation of 30 dynamic groups from the Pre-Diploma cohort, selected from 15 classes, each embarking on a journey to explore and illuminate various aspects of global cultures. Their presentations were not just displays of academic research; they were heartfelt narratives that brought distant cultures right to the heart of UiTMCPP, showcasing their linguistic prowess and their dedication to embracing the vastness of human diversity.